PEMBINAAN NARAPIDANA SEBAGAI UPAYA MENCEGAH TERJADINYA RESIDIVIS DI LEMBAGA PEMASYARAKATAN KELAS 1 MAKASSAR - H. Bolu. H.B; A. Erang (Journal of Management and Social Sciences, 2022)
The purpose of this study is to find out how the coaching process in correctional institutions in an effort to prevent recidivism also explores the factors that cause recidivism. This research was conducted at the Makassar Class I Penitentiary. This study uses empirical and qualitative research methods, namely by means of the field in the form of interviews, observations, and sources taking data directly from the Makassar Class I Correctional Institution. coaching is focused on efforts to instill spiritual values and mental attitudes that are prioritized by Correctional Institutions so that it is very useful because after serving a period of detention as a convict they can start a new life in accordance with the objectives of coaching that are obtained in Class I Correctional Institutions in Makassar and can be implemented in social life.